Diabetes as a risk factor for acute coronary syndrome in women compared with men: a meta‐analysis, including 10 856 279 individuals and 106 703 acute coronary syndrome events. Issue 5 (23rd February 2017) - Dong, Xue; Cai, Rongrong; Sun, Jie; Huang, Rong; Wang, Pin; Sun, Haixia; Tian, Sai; Wang, Shaohua
Abstract: Background: Diabetes mellitus is a significant cause of death and disability worldwide and is a strong risk factor for acute coronary syndrome (ACS). Whether diabetes confers the same excess risk of ACS in both sexes is unknown. Therefore, we undertook a meta‐analysis to estimate the relative risk (RR) for ACS associated with diabetes in men and women. Methods: We systematically searched PubMed, Embase, and Cochrane Library databases for both case‐control and cohort studies published between January 1, 1966, and January 1, 2015. Studies were included if they reported sex‐specific estimates of the RR, hazard ratio, or odds ratio for the association between diabetes and ACS. We pooled the sex‐specific RR and the ratio between women and men using a random‐effect model with inverse‐variance weighting. Results: We included 9 case‐control and 10 cohort studies with data for 10 856 279 individuals and at least 106 703 fatal and nonfatal ACS events. The pooled maximum‐adjusted RR of ACS associated with diabetes was 2.46 (95% CI, 1.92‐3.17) in women and 1.68 (95% CI, 1.39‐2.04) in men. In patients with diabetes compared with those without diabetes, women had a significantly greater risk of ACS—the pooled women‐to‐men RR and the ratio of relative risks was 1.38 (95% CI, 1.25‐1.52; P  < .001), with no evidence of publication bias. Conclusions: The excess risk of ACS associated with diabetes is significantly higher in women than in men. This finding may be explained by more adverse cardiovascular risk profiles and suggests that further work is needed to clarify the relevant biological, behavioural, and social mechanisms.